The Sixth Borough: Metaphorizations of the Water in New York City's Comprehensive Waterfront Plan Vision 2020 and Foer's "The Sixth Borough". Issue 3 (27th May 2019) - Ameel, Lieven
ABSTRACT: In visions of future New York City, the waterfront appears as a highly symbolic space, a site of possibility and transformation, imbued with complex cultural meanings. Crucial for the understanding of the urban waterfront and its development are the metaphors used to describe changing relationships to it, across genres. This article focuses on one specific metaphorization of the watery edge of New York City, that of the "Sixth Borough." It examines the 2011 New York comprehensive waterfront plan Vision 2020 and Jonathan Safran Foer's short story "The Sixth Borough, " part of the novel Extremely Loud & Incredibly Close, but published as a separate short story in the New York Times (2004, 2005). Read side by side, these texts offer a compelling—if contradictory—view of how the words to describe the city engage with eruptions in the material world.